Presence of the Academy of Sciences in Cienfuegos (19th century - 21st century) - Alfredo Darío Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
The article relates the first associations with scientific purposes that worked in Cienfuegos during the second half of the 19th century, with emphasis on the Medical Association of Cienfuegos and the Medical-Pharmaceutical Center of Cienfuegos and its relations with the Royal Academy of Medical Sciences, Physical and Natural of Havana, in addition the first professionals from Cienfuegos who worked as Academic "reporters" are mentioned. It refers to the constitution and integration of the first Provincial Technical Advisory Council of Cienfuegos in 1981, and the current, governed by the Ministry of Science, Technology and Environment since its emergence in 1994 to the present times. Professionals who have been chosen to represent Cienfuegos in the Cuban Academy of Sciences in the different periods and the foundation of the Alternative Office of the Academy of Sciences in Cienfuegos in the year 2000, as well as the sponsor institution of the Hospital Dr Gustavo Aldereguía Lima, in 2004, are mentioned. It explains the frequent participation of other Academics -especially those living in the capital- in various activities in the province. The constitution of the Provincial Branch of the Cuban Academy of Sciences in Cienfuegos on April 25, 2019, and the challenges that lie ahead are discussed.